2022
DOI: 10.1111/1440-1681.13672
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin receptor‐neprilysin inhibitor attenuates cardiac hypertrophy and improves diastolic dysfunction in a mouse model of heart failure with preserved ejection fraction

Abstract: LCZ696, an angiotensin receptor–neprilysin inhibitor, has shown promising clinical efficacy in patients with heart failure (HF) with reduced ejection fraction. However, its potential effects on heart failure with preserved ejection fraction (HFpEF) are still not fully understood. We evaluated the effect of LCZ696 on HFpEF in transverse aortic constriction mice and compared it with the effect of the angiotensin receptor blocker, valsartan. We found that LCZ696 improved cardiac diastolic function by reducing ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Studies have shown that sacubitril-valsartan improved cardiac diastole function by reducing ventricular hypertrophy and fibrosis in mice. The potential underlying mechanism is that sacubitril-valsartan effectively suppresses the transmission of signals involved in calcium-mediated calcineurin-nuclear factor of activated T cell pathways [ 23 ].…”
Section: Pharmacological and Non-pharmacological Treatments Of Hfpefmentioning
confidence: 99%
“…Studies have shown that sacubitril-valsartan improved cardiac diastole function by reducing ventricular hypertrophy and fibrosis in mice. The potential underlying mechanism is that sacubitril-valsartan effectively suppresses the transmission of signals involved in calcium-mediated calcineurin-nuclear factor of activated T cell pathways [ 23 ].…”
Section: Pharmacological and Non-pharmacological Treatments Of Hfpefmentioning
confidence: 99%
“…The European Society of Cardiology's medical guidelines have recently been amended. They currently recommend (Class I) the use of LCZ696, an angiotensin receptor-neprilysin inhibitor (ARNI), to minimize mortality as well as morbidity among individuals with HF with reduced ejection fraction (HFrEF) [ 2 , 3 ]. LCZ696 is a composite of sacubitril and valsartan, possessing the molecular components of both drugs [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…They currently recommend (Class I) the use of LCZ696, an angiotensin receptor-neprilysin inhibitor (ARNI), to minimize mortality as well as morbidity among individuals with HF with reduced ejection fraction (HFrEF) [ 2 , 3 ]. LCZ696 is a composite of sacubitril and valsartan, possessing the molecular components of both drugs [ 3 ]. The combined medication of sacubitril/valsartan has the ability to hinder the activity of both neprilysin and angiotensin receptors.…”
Section: Introductionmentioning
confidence: 99%